2017
DOI: 10.28945/3855
|View full text |Cite
|
Sign up to set email alerts
|

Learning Foreign Languages Using Mobile Applications

Abstract: Aim/PurposeThis study examines how the use of a Mobile Assisted Language Learning (MALL) application influences the learners' attitudes towards the process of learning, and more specifically in voluntary and mandatory environments. Background Mobile devices and applications, which have become an integral part of our lives, are used for different purposes, including educational objectives. Among others, they are used in the process of foreign language acquisition. The use of a MALL application to learn foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 16 publications
(37 reference statements)
1
20
0
2
Order By: Relevance
“…It made it easier for students to find and learn course-related content online, although a few of them expressed their rejection as they did not associate "childish" avatars with a formal university learning environment. Gafni et al (2017) also observed L2 students' positive attitudes towards using Duolingo as a parallel support of their language courses. Although the study was short, students expressed their satisfaction towards the app as a learning enhancer.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…It made it easier for students to find and learn course-related content online, although a few of them expressed their rejection as they did not associate "childish" avatars with a formal university learning environment. Gafni et al (2017) also observed L2 students' positive attitudes towards using Duolingo as a parallel support of their language courses. Although the study was short, students expressed their satisfaction towards the app as a learning enhancer.…”
Section: Resultsmentioning
confidence: 70%
“…Practically all of them were conducted with the help of free applications that can be easily accessed or downloaded from the Internet and used whether on a computer or a mobile device. Most experiments incorporated a gamified resource especially created for the study (Berns, et al & Dodero, 2016;Cardoso, et al 2017;Liu, et al 2016;Palomo-Duarte et al, 2016;Perry, 2015), whereas Duolingo and Kahoot were the most popular commercial apps (Bustillo, et al 2017;Gafni, et al 2017;Hung, 2017;Iaremenko, 2017;Mateo-Gallego & Ruiz Yepes, 2018;Munday, 2016). English stands out among the second languages studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Translation exercises of sentences and words are the delivery method of this application. Moreover, instructors can see logs and progress to keep an eye on the students ( Gafni, Achituv & Rahmani, 2017 ). A mobile-based gaming approach for English grammar and vocabulary learning ‘Save the princess with Teddy’ was developed and students’ learning achievement with gameplay at different levels was analyzed.…”
Section: Assessment and Discussion Of Research Questionsmentioning
confidence: 99%
“…Learning a new language can be so. Therefore, playing with the words and competing versus others can be very encouraging, thus stimulating the learning process» (Ruti Gafni, 2017). The user has the opportunity to test the learned words by performing various exercises: word-combining, selecting the right word, spelling, etc.…”
Section: Using Electronic Teaching Resourcesmentioning
confidence: 99%